2010
DOI: 10.1089/ast.2010.0513
|View full text |Cite
|
Sign up to set email alerts
|

Biogenicity of Morphologically Diverse Carbonaceous Microstructures from the ca. 3400 Ma Strelley Pool Formation, in the Pilbara Craton, Western Australia

Abstract: Morphologically diverse structures that may constitute organic microfossils are reported from three remote and widely separated localities assigned to the ca. 3400 Ma Strelley Pool Formation in the Pilbara Craton, Western Australia. These localities include the Panorama, Warralong, and Goldsworthy greenstone belts. From the Panorama greenstone belt, large (> 40 μm) lenticular to spindle-like structures, spheroidal structures, and mat-forming thread-like structures are found. Similar assemblages of carbonaceous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
88
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(93 citation statements)
references
References 68 publications
4
88
1
Order By: Relevance
“…Current interpretations of the diversity of Earth's earliest life come predominantly from stromatolites (e.g., Lowe, 1980;Walter et al, 1980;Byerly et al, 1986;Hofmann et al, 1999;Allwood et al, 2006Allwood et al, , 2007Allwood et al, , 2009Allwood et al, , 2010Hickman, 2012), organic microfossils of prokaryotes and biofilms (e.g., Awramik et al, 1983;Walsh andLowe, 1985, 1999;Walsh, 1992;Hofmann, 2004;Schopf et al, 2007;Schopf and Bottjer, 2009;Sugitani et al, 2010;Wacey et al, 2011Wacey et al, , 2012Hickman 2012), and isotopic signatures of carbon and sulfur (e.g., Shen et al, 2001Shen et al, , 2009Ueno et al, 2006Ueno et al, , 2008Wacey et al, 2010). Microbially induced sedimentary structures (MISS) provide an additional way to decode life in ancient sediments (review in Noffke, 2010).…”
Section: Microbially Induced Sedimentary Structures and The Early Recmentioning
confidence: 99%
“…Current interpretations of the diversity of Earth's earliest life come predominantly from stromatolites (e.g., Lowe, 1980;Walter et al, 1980;Byerly et al, 1986;Hofmann et al, 1999;Allwood et al, 2006Allwood et al, , 2007Allwood et al, , 2009Allwood et al, , 2010Hickman, 2012), organic microfossils of prokaryotes and biofilms (e.g., Awramik et al, 1983;Walsh andLowe, 1985, 1999;Walsh, 1992;Hofmann, 2004;Schopf et al, 2007;Schopf and Bottjer, 2009;Sugitani et al, 2010;Wacey et al, 2011Wacey et al, , 2012Hickman 2012), and isotopic signatures of carbon and sulfur (e.g., Shen et al, 2001Shen et al, , 2009Ueno et al, 2006Ueno et al, , 2008Wacey et al, 2010). Microbially induced sedimentary structures (MISS) provide an additional way to decode life in ancient sediments (review in Noffke, 2010).…”
Section: Microbially Induced Sedimentary Structures and The Early Recmentioning
confidence: 99%
“…Sugitani et al (2010) showed that Raman spectra collected on carbonaceous microstructures from the 3.4 Ga Strelley Pool Formation had I D /I G ratios varying between 1.25 and 1.94. Micrometer-scale heterogeneities in CM may be explained by a variety of mechanisms, such as micrometer-scale differences in precursor chemistry of CM, and subsequently dissimilar alteration pathways of the different precursor material, allochthonous CM, or emplacement of CM during multiple hydrothermal pulses at different temperatures.…”
mentioning
confidence: 99%
“…The importance of a reducing atmosphere is that the action of various energy sources on reduced C gas mixtures, including CO and CH 4 , results in the formation of a variety of more complex organic compounds, whereas using CO 2 this chemistry is less productive (Miller Sugitani et al 2010) and Schlesinger 1984;Miller 1983a, 1983b). In the presence of nitrogen, in the form of N 2 or NH 3 , important biological compounds including amino acids, purines and pyrimidines can be formed (Cleaves and Lazcano 2009).…”
Section: The Earth Early Atmospherementioning
confidence: 99%